Decoding Personal Goals of Indonesian Gen Z: Insights from Big Five Personality and Social Cognitive Career Theory - Adelia Rizqina Sadalia; Insany Fitri Nurqamar; Nur Siti Rahma; Amelda Sari; Nurul Mutmainna; Meysa Dwi Andini (Business Management Analysis Journal (BMAJ), 2026)
Generation Z will become the largest workforce in Indonesia, but they face career uncertainty, psychological pressure, and a tendency to job hop. This study analyzes the influence of the Big Five personality traits on Generation Z's personal goals, mediated by self-efficacy and outcome expectations, and explores the meaning of personal goals qualitatively. A sequential explanatory mixed-methods design was used, involving an online survey of 400 respondents from the 10 most populous provinces and in-depth interviews with selected informants. The analysis shows that the Big Five personality traits do not have a direct effect, but are significant through mediating factors. Qualitatively, personal goals are understood not only as economic stability, but also as life balance and self-actualization. The findings emphasize the importance of career planning that takes into account Generation Z's self-confidence and experience.